Northeast Pacific record of the Paleogene genus Pseudoperissolax (Neogastropoda: Muricidae: Muricinae) and its paleobiogeography. (16th November 2015) - Squires, Richard L.
Abstract: The geologic record of the shallow-marine gastropod genus Pseudoperissolax Clark, 1918 is documented in detail for the first time in a region of the northeast Pacific extending from southwestern Washington to northern Baja California, Mexico. This genus, which has been erroneously equated with the nomen dubium Perrisolax Gabb, 1861, comprises a very small group of species whose supra-generic ranking has been inconsistent. Pseudoperissolax is placed here in family Muricidae Rafinesque, 1815 and subfamily Muricinae Rafinesque, 1815 based on the presence of varices, a club-shaped last whorl with noded carinae, and a long siphonal canal. The genus is represented in the northeast Pacific by the late Paleocene Pseudoperissolax tricarnatus (Weaver, 1905 ) and the late Paleocene to late Eocene Pseudoperissolax blakei (Conrad, 1855 ). Pseudoperissolax was a warm-water gastropod that most likely originated during the Late Cretaceous (Maastrichtian) in Madagascar and also questionably spread during this time to southern New Zealand. Its certain geologic range is early Paleocene to earliest Oligocene, with occurrences in western Kamchatka, southern Japan, southwestern Washington, southwestern Oregon, southern California, northern Baja California, Mexico, southern Alabama, and Nuevo León, northeastern Mexico. Whether Pseudoperissolax migrated into the northeast Pacific from Kamchatka or from Alabama and Mexico cannot be determined with certainty. The decline and eventual extinction of the genus coincided with the global-cooling event at the end of the Eocene.